Reduced local segregation of single‐subject gray matter networks in adult PTSD - Niu, Running; Lei, Du; Chen, Fuqin; Chen, Ying; Suo, Xueling; Li, Lingjiang; Lui, Su; Huang, Xiaoqi; Sweeney, John A.; Gong, Qiyong (Human brain mapping, 2018)
To psychoradiologically investigate the topological organization of single‐subject gray matter networks in patients with PTSD. Eighty‐nine adult PTSD patients and 88 trauma‐exposed controls (TEC) underwent a structural T1 magnetic resonance imaging scan. The single‐subject brain structural networks were constructed based on gray matter similarity of 90 brain regions. The area under the curve (AUC) of each network metric was calculated and both global and nodal network properties were measured in graph theory analysis. We used nonparametric permutation tests to identify group differences in topological metrics. Relationships between brain network measures and clinical symptom severity were analyzed in the PTSD group. Compared with TEC, brain networks of PTSD patients were characterized by decreased clustering coefficient ( C p ) ( p = .04) and local efficiency ( E loc ) ( p = .04). Locally, patients with PTSD exhibited altered nodal centrality involving medial superior frontal (mSFG), inferior orbital frontal (iOFG), superior parietal (SPG), middle frontal (MFG), angular, and para‐hippocampal gyri ( p < .05, corrected). A negative correlation between the segregation ( C p ) of gray matter and functional networks was found in PTSD patients but not the TEC group. Analyses of topological brain gray matter networks indicate a more randomly organized brain network in PTSD. The reduced segregation in gray matter networks and its negative relation with increased segregation in the functional network indicate an inverse relation between gray matter and functional changes. The present psychoradiological findings may reflect a compensatory increase in functional network segregation following a loss of segregation in gray matter networks.